Impact of Capital Structure on Firm Performance: Evidence from Material Sector Listed Companies in Sri Lanka During the Economic Crisis - Ganeshamoorthy, Thaneshan; Krishnasamy, Tharsika (Copernican Journal of Finance & Accounting, 2026)
The ongoing economic crisis in Sri Lanka has created significant obstacles for companies in obtaining and managing debt and equity financing, thereby shaping their capital structure choices. These decisions play a vital role in determining a firm’s financial health and long-term sustainability. However, existing empirical and theoretical studies present conflicting findings on this relationship. In light of this, the present study investigates the impact of capital structure on the firm performance of materials companies listed on the Colombo Stock Exchange in Sri Lanka by examining the Total Debt Ratio (TDR) and Long-Term Debt Ratio (LTDR) as indicators of capital structure and evaluating performance through Return on Assets (ROA) and Return on Equity (ROE). The analysis is based on panel data collected from the annual reports of 18 prominent companies covering the period from 2020/21 to 2024/25. Pearson’s correlation analysis and Random Effects Generalized Least Squares regression are applied to evaluate the data. The findings reveal that the TDR negatively and significantly impacts both ROA and ROE, suggesting that higher debt levels adversely affect profitability. Conversely, the LTDR does not significantly impact either ROA or ROE, indicating that long-term debt does not substantially influence profitability. The study’s drawbacks encompass the use of a restricted range of factors to evaluate capital structure and financial performance, in addition to a comparatively small sample size. Notwithstanding these constraints, the study offers significant insights for investors, managers, legislators, and business decision-makers regarding the impact of capital structure on financial performance.